Development of Student Character Education through Children Literacy in Teaching and Learning Practices - Ulfa Kurniasih; Azizatul Khairi (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2021)
Education is essentially aimed at improving the human beings who can be useful to himself, communities, and even countries. Based on this, the problem in this paper is the extent to which the role of learning Indonesian culture in the formation of student character. One of the cultures of Indonesia is the literacy of children or children's fairy tales that almost always exist in every region. Through this, the purpose of this paper is to know the importance of incorporating elements of culture through the literacy of children in the practice of teaching and learning in the formation of student characters. Given the importance of character formation of students in producing people who are not only smart but also virtuous and morally good, then one way to develop character education is to preserve the culture of Indonesia. The embodiment in the formation of cultural-based characters, especially the literacy of children, by incorporating elements or ideas and cultural messages contained in it in the process of teaching and learning. This is expected to be one of the guidelines in shaping the character of the students. In the end this paper shows that the preservation of Indonesian culture through children's literacy is still very relevant in terms of instilling and building the character of students in the learning process in the school environment